Complex 3D scan trajectories for industrial cone-beam computed tomography using a hexapod - Butzhammer, Lorenz; Hausotte, Tino (Measurement Science & Technology, 2021)
Industrial x-ray computed tomography (CT) represents an established measurement technique in the field of nondestructive testing and dimensional metrology. However, the measurement accuracy is sometimes limited by measurement artifacts that cannot be avoided using a standard circular scan trajectory. This problem can be addressed with the aid of flexible 3D trajectories, but up to date, the application of these is mainly restricted to special CT devices using robot arms. In this paper, we present results using a hexapod as an additional positioning system in a commercial industrial CT scanner. In addition to the 360 rotation, task-specific tilting of the part during the scan is possible in this way. We used and adapted geometry calibration procedures based on a multi-sphere reference object to enable reconstruction with high accuracy. Using a demonstrator test fixture with high absorbing elements, we show that severe metal and truncation artifacts can be avoided for a region-of-interest scan. Furthermore, cone-beam artifacts, which are inherent to circular scan trajectories, can be reduced significantly. Using measurement objects that can be measured well with a circular trajectory, we found that applying a 3D trajectory leads to dimensional measurement deviations in the same range or even lower than those of a circular trajectory. This suggests that the pose repeatability of the hexapod is sufficient to perform complex scan paths without general loss of accuracy. The obtained results could be relevant for end users of conventional CT scanners, as upgrading existing devices is in principle possible. The presented investigations form the basis for the application of trajectory optimization algorithms.<br
Keywords: computed tomography; dimensional metrology; scan trajectory; hexapod